2022
DOI: 10.1136/bmjopen-2022-064716
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and its associated factors among healthcare workers and the general working population in Japan during the COVID-19 pandemic: a nationwide cross-sectional internet-based study

Abstract: ObjectivesTo examine the prevalence and the associated factors of burnout among both healthcare workers (HCWs) and the general working population, which has not yet been unknown, using large-scale, nationwide data.DesignCross-sectional internet-based study.SettingNationwide internet survey conducted between 8 and 26 February 2021 in Japan.ParticipantsWorkers aged 20–64 years. We classified the workers as HCWs and the general working population.ExposuresDemographic characteristics (age, sex and marital status),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…In a systematic review and meta-analysis of the psychological impact of COVID-19 on Chinese healthcare workers in early 2020 (12), pooled prevalence rates of anxiety, depression, and sleep disturbances were 17% (13-21%), 15% (13-16%), and 15% (7-23%), respectively. Tong et al (35) reported the prevalence of anxiety and depression in FHWs during the outbreak period and regular period was 1.6 and 13.1% and 6.1 and 8.1%, respectively. In our study, the trend of "less depressed, more anxious" from outbreak to regular period was similar to Tong et al 's findings, although the prevalence rates of both symptoms were higher in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review and meta-analysis of the psychological impact of COVID-19 on Chinese healthcare workers in early 2020 (12), pooled prevalence rates of anxiety, depression, and sleep disturbances were 17% (13-21%), 15% (13-16%), and 15% (7-23%), respectively. Tong et al (35) reported the prevalence of anxiety and depression in FHWs during the outbreak period and regular period was 1.6 and 13.1% and 6.1 and 8.1%, respectively. In our study, the trend of "less depressed, more anxious" from outbreak to regular period was similar to Tong et al 's findings, although the prevalence rates of both symptoms were higher in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational burnout among medical personnel is often higher than in the general population ( 36 ). Since the start of the COVID-19 pandemic, studies of burnout among front-line and non-front-line HWs have shown a high burnout rate ( 20 , 37 – 41 ), and these HWs often have more emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence exists on the prevalence of burnout in the general working population and across occupational industries ( 40 ). To our knowledge, this study is the first in the region to investigate the prevalence of employee burnout in the general working adult population of Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout research was initially focused on people-oriented occupations where a service provider directly deals with the recipient. The healthcare sector is people-oriented and has experienced increased burnout compared to the general population [ 10 12 ]. Even within the healthcare sector, burnout has been well-documented among doctors, nurses, and frontline workers.…”
Section: Introductionmentioning
confidence: 99%